Spread of Cholera with Newer Clones of Vibrio cholerae O1 El Tor, Serotype Inaba, in India - Dutta, B. (American Society for Microbiology, 2006)
During 2004 and 2005, cholera was recorded in 15 states of India, with 7 outbreaks. The newly emerged Vibrio cholerae O1 Inaba had a different antibiogram and ribotype, different pulsotypes, and different mutations in the wbeT gene. Due to the absence of serogroup O139, the Inaba serotype may have acquired the potential to affect the population at large.